Relationship of Mothers’ Psychological Status with Development of Kindergarten Children - SAJEDI, Firoozeh; AHMADI DOULABI, Mahbobeh; VAMEGHI, Roshanak; MAZAHERI, Mohammad Ali; AKBARZADEH BAGHBAN, Alireza (Iranian Journal of Child Neurology, 2016)
How to Cite This Article: Firoozeh Sajedi F, Ahmadi Doulabi M, Vameghi R, Mazaheri MA, Akbarzadeh Baghban AR. Relationship of Mothers’ Psychological Status with Development of Kindergarten Children. Iran J Child Neurol. Summer 2016; 10(3):61-72. Abstract Objective Given the importance of children’s development and the role of psychological status of mothers in this regard, this study investigated the relationship of mothers’ psychological status (stress, anxiety and depression) with the development of children aged 36-60 months. Materials & Methods This descriptive study was performed on 1036 mothers and their children, aged 36 to 60 months, in different kindergartens in Tehran City, Iran, in 2014-2015. Participants were selected through multi-stage random sampling. The following instruments were used in this study: A demographic and obstetric specification questionnaire, children specification questionnaire, the Beck Depression Inventory, Spiel Berger Test, Perceived stress questionnaire and the Ages and Stages Questionnaire to determine the status of the children’s development. Data were analyzed using SPSS20 software, Mann-Whitney; independent t-test and logistic-Regression model were used. Results The prevalence of developmental delay in children aged 36-60 months was 16.2%. The independent t-test showed a relationship between maternal stress and developmental delay in children. The Mann-Whitney test revealed a significant relation between mothers’ depression level and developmental delay in their children. There was a significant relation between trait anxiety and developmental delay in children. Moreover, a significant relation was found between maternal stress and developmental delay in fine motor skills. The logistic regression model showed a significant relationship of child gender, economic and social states with developmental delay. Conclusion This study showed mothers’ psychological status probably is an effective factor in developmental delay. The assessment of mothers’ psychological status is suggested for early interventions. References Irwin LG, Siddiqi A, Hertzman C. Early child development: a powerful equalizer. Final report to the WHO Commission on social determinants of health, Geneva. 2007. Guralnick MJ. Early Intervention for Children with Intellectual Disabilities: Current Knowledge and Future Prospects. J Appl Res Intellect Disabil 2005;18(4):313-24. Marmot M, Friel S, Bell R, Houweling TA, Taylor S. Commission on Social Determinants of Health. Closing the gap in a generation: health equity through action on the social determinants of health. Lance 2008 Nov 14;372(9650):1661-1669. Boyle CA, Boulet S, Schieve L, Cohen RA, Blumberg SJ, Yeargin-Allsopp M, Visser S, Kogan MD. Trends in the Prevalence of Developmental Disabilities in US Children, 1997–2008. Pediatrics 2011; 27: 1034-1042. Sherr EH, Shevell MI. Global developmental delay and mental retardation/ intellectual disability. In: Swaiman KF, Ashwal S, Ferriero DM, Schor NF.eds Pediatric neurology:principles and practice. 5th ed. Philadelphia: Elsevier Saunders, 2012:554–74. Al-Naddawi M, Ibraheem MF, Alwan SH, Causes of Global Developmental Delay in Children Welfare Teaching Hospital-Baghdad. IPMJ 2013;12(3):383-9. Vohr BR, O’Shea M, Wright LL, editors. Longitudinal multicenter follow-up of high-risk infants: why, who, when, and what to assess. Seminars in Perinatology; 2003: Elsevier. Rydz D, Srour M, Oskoui M, Marget N, Shiller M, Birnbaum R, et al. Screening for developmental delay in the setting of a community pediatric clinic: a rospective assessment of parent-report questionnaires. PEDIATRICS 2006;118(4):e1178-e86. Glascoe FP. Early detection of developmental and behavioral problems. Pediatr Rev 2000;21(8):272-80. Potijk MR, Kerstjens JM, Bos AF, Reijneveld SA, de Winter AF. Developmental delay in moderately preterm-born children with low socioeconomic status: risks multiply. Pediatrics 2013;163(5):1289-95. de Moura DR, Costa JC, Santos IS, Barros AJ, Matijasevich A, Halpern R, et al. Risk factors for suspected developmental delay at age 2 years in a Brazilian birth cohort. Paediatr Perinat Epidemiol 2010;24(3):211-21. Poon JK, Larosa AC, Pai GS. Developmental delay: timely identification and assessment. Indian Pediatr 2010;47(5):415-22. Tervo RC. Identifying patterns of developmental delays can help diagnose neurodevelopmental disorders. Clin Pediatr 2006;45(6):509-17. Afraz S, Ahmadi M, Sajedi F, Akbarzadeh Baghban A. Development Status of 4-24 Months Children Born to Teenage Mothers Referred to Health Care Centers in Yasuj, 2013. Yumsj 2015;20(3):253-63. Shahshahani S, Vameghi R, Azari N, Sajedi F, Kazemnejad A. Comparing the Results of Developmental Screening of 4-60 Months Old Children in Tehran Using ASQ & PDQ. Iran Rehab J 2011 Jul 15;9:3-7. Shaahmadi F, Khushemehri G, Arefi Z, Karimyan A, Heidari F. Developmental Delay and Its Effective Factors in Children Aged 4 to12 Months. In J Pediatr 2015 Jan 1;3(1.1):396-402. Karami K, Abbasi L, Moridi F, Falah F, Bayat Z, Pourvakhshoori N. Evaluation criteria and factors associated with the development of one year old children in Khorramabad. Iran J Pediatr 2015;1(3):57-64. Dorre F, Fattahi Bayat G. Evaluation of children’s development (4-60mo) with history of NICU admission based on ASQ in Amir kabir Hospital, Arak. J Ardabil Uni Med Sci 2011 Jun 15;11(2):143-50. Shahshahani S, Vameghi R, Azari N, Sajedi F, A. K. Developmental screening for children 60-4 months in Tehran using the Denver Developmental Screening Test 2 and Ages and Stages Questionnaires. Quarterly J Rehab 2011; 12 (3):65-71. Persha A, Arya S, Nagar R, Behera P, Verma R, Kishore M. Biological and psychosocial predictors of developmental delay in persons with intellectual disability: retrospective case-file study. APDRJ 2007;18(1):93-100. Sanders B, Schneiderman JU, Loken A, Lankenau SE, Bloom JJ. Gang youth as a vulnerable population for nursing intervention. Public Health Nurs 2009;26(4):346-52. To T, Guttmann A, Dick PT, Rosenfield JD, Parkin PC, Tassoudji M, et al. Risk markers for poor developmental attainment in young children: results from a longitudinal national survey. Arch Pediatr Adolesc Med 2004;158(7):643-9. Sameroff AJ, Seifer R, Barocas R, Zax M, Greenspan S. Intelligence quotient scores of 4-year-old children: Social-environmental risk factors. Pediatrics 1987;79(3):343-50. Delgado CE, Vagi SJ, Scott KG. Identification of early risk factors for developmental delay. Exceptionality 2007;15(2):119-36. Huggenberger HJ, Suter SE, Blumenthal TD, Schachinger Maternal social stress modulates the development of prepulse inhibition of startle in infants. Dev Cogn Neurosci 2013;3:84-90. Ceballo R, McLoyd VC. Social support and parenting in poor, dangerous neighborhoods. Child Dev 2002:1310-21. Conners-Burrow NA, Johnson B, Whiteside-Mansell Maternal substance abuse and children’s exposure to violence. Pediatrics Nursing 2009;24(5):360-8. Propper C, Rigg J. Socio-economic status and child behaviour: evidence from a contemporary UK cohort. Lse Sticerd Research Paper No Case 125. 2007. Berg-Nielsen TS, Vika A, Dahl AA. When adolescents disagree with their mothers: CBCL-YSR discrepancies related to maternal depression and adolescent self-esteem. Child Care Health Dev 2003;29(3):207-13. Koutra K, Chatzi L, Bagkeris M, Vassilaki M, Bitsios P, Kogevinas M. Antenatal and postnatal maternal mental health as determinants of infant neurodevelopment at 18 months of age in a mother–child cohort (Rhea Study) in Crete, Greece. Soc Psychiatry Psychiatr Epidemiol 2013;48(8):1335-45. Ordway MR. Depressed mothers as informants on child behavior: Methodological issues. Res Nurs Health 2011;34(6):520-32. Field T. Infants of depressed mothers. Infant Behav Dev 1995;18(1):1-13. Herring S, Gray K, Taffe J, Tonge B, Sweeney D, Einfeld Behaviour and emotional problems in toddlers with pervasive developmental disorders and developmental delay: associations with parental mental health and family functioning. J Intellectual Disabil Res 2006;50(12):874-82. Jakšić N, Ivezić E, Jokić-Begić N, Surányi Z, Stojanović-Špehar S. Factorial and diagnostic validity of the Beck Depression Inventory-II (BDI-II) In Croatian primary health care. J Clin Psychol Med Settings 2013;20(3):311-22. Hall BJ, Hood MM, Nackers LM, Azarbad L, Ivan I, Corsica J. Confirmatory factor analysis of the Beck Depression Inventory-II in bariatric surgery candidates. Psychol Assessment 2013;25(1):294. Razavi SH, Razavi-Ratki SK, Nojomi MM, Namiranian N. Depression and general anxiety in the prisoner of war’s children: a cross sectional study. Med J Islam Repub Iran 2012;26(4):179. Ghassemzadeh H, Mojtabai R, Karamghadiri N, Ebrahimkhani N. Psychometric properties of a Persian-language version of the Beck Depression Inventory-Second edition: BDI-II-PERSIAN. Depress Anxiety 2005;21(4):185-92. Cohen S, Kamarck T, Mermelstein R. A global measure of perceived stress. J Health Soc Behav 1983:385-96. Bastani F, Rahmatnejad L, Jahdi F, Haghani H. Breastfeeding self efficacy and perceived stress in primiparous mothers. IJN 2008;21(54):9-24. Bech P, Gormsen L, Loldrup D, Lunde M. The clinical effect of clomipramine in chronic idiopathic pain disorder revisited using the Spielberger State Anxiety Symptom Scale (SSASS) as outcome scale. J Affect Disord 2009;119(1):43-51. Court H, Greenland K, Margrain TH. Measuring Patient Anxiety in Primary Care: Rasch Analysis of the 6-item Spielberger State Anxiety Scale. Value in Health 2010;13(6):813-9. Nasiri AF, Salmalian H, Haji AM, Ahmadi AM. Association between prenatal anxiety and spontaneous preterm birth. JBUMS 2009;11(4):42-48. Shamaeian Razavi N, Bahri Binabaj N, Hoseiny Shahidy L, PourHeidari M. The effect of maternal position on labor pain. Ofogh-e-Danesh Journal 2006;12(2):16-21. Masoumi R, Lamieian M, Ghaedi S. Role of oxytocin in anxiety in the normal parturition. Zah J Res Med Sci 2008; 10(1):53-58. Kaviani H, Ahmadi Abhari A. Prevalence of anxiety disorders in Tehran city. Iran J Psychiatry Clin Psychol 2003;8(3):4-11. Zhang J, Gao Q. Validation of the trait anxiety scale for state-trait anxiety inventory in suicide victims and living controls of Chinese rural youths. Arch Suicide Res 2012;16(1):85-94. Elbers J, Macnab A, McLeod E. Article originale. Can J Rural Med 2008;13(1). Yu LM, Hey E, Doyle LW, Farrell B, Spark P, Altman DG, et al. Evaluation of the Ages and Stages Questionnaires identifying children with neurosensory disability the Magpie Trial follow-up study. Acta Paediatrica 2007;96(12):1803-8. Lindsay NM, Healy GN, Colditz PB, Lingwood BE. Use of the Ages and Stages Questionnaire to predict outcome after hypoxic-ischaemic encephalopathy in the neonate. J Paediatr Child Health 2008;44(10):590-5. Squires J, Bricker D, Potter L. Revision of a parent-completed developmental screening tool: Ages and Stages Questionnaires. J Pediatr Psychol 1997;22(3):313-28. Glascoe FP. Screening for developmental and behavioral problems. Ment Retard Dev Disable Res Rev 2005;11(3):173-9. Richter J, Janson H. A validation study of the Norwegian version of the Ages and Stages Questionnaires. Acta Paediatr 2007;96(5):748-52. Vameghi R, Sajedi F, Mojembari AK, Habiollahi A, Lornezhad HR, Delavar B. Cross-cultural adaptation, validation and standardization of Ages and Stages Questionnaire (ASQ) in Iranian children. Iran J Publ Health 2013;42(5):522. Chiang T-L, Lin S-J, Shu B-C. Parental mental health and child development from six to thirty-six months in a birth cohort study in Taiwan. J Perinat Med 2009;37(4):397-402. Benjamin J, Sadock, Virginia A. Kaplan comprehensive Text book of psychiatry,7 th ed:Lippincott Williams.2000,1284-1338. Sajadi H, Vameghi M, Setare forozan A, Rafiey H, Mohgheghee Kamal SH, Nosrat abadi M. Prevalence, risk factors and interventions of depression during pregnancy in Iranian Studies (1997-2011): A systematic review. North Khorasan Univ Med Sci 2013;5(2):521-30. Ali NS, Mahmud S, Khan A, Ali BS. Impact of postpartum anxiety and depression on child’s mental development from two peri-urban communities of Karachi, Pakistan: a quasi-experimental study. Bmc Psychiatrry 2013;13(1):274. Hadley C, Tegegn A, Tessema F, Asefa M, Galea S. Parental symptoms of common mental disorders and children’s social, motor, and language development in sub-Saharan Africa. Ahb Ann Hum Biol 2008;35(3):259-75. Brennan PA, Hammen C, Andersen MJ, Bor W, Najman JM, Williams GM. Chronicity, severity, and timing of maternal depressive symptoms: relationships with child outcomes at age 5. Dev Psychol 2000;36(6):759. Coyl D, Roggman L, Newland L. Stress, maternal depression and negative mother-infant interactions in relation to infant attachment. Infant Ment Health J 2002; 23: 145-163. Brouwers EP, van Baar AL, Pop VJ. Maternal anxiety during pregnancy and subsequent infant development. Infant Behav Dev 2001;24(1):95-106. McLearn KT, Minkovitz CS, Strobino DM, Marks E, Hou W. The timing of maternal depressive symptoms and mothers’ parenting practices with young children: implications for pediatric practice. Pediatrics 2006;118(1):e174-e82. Van der Toorn SL, Huizink AC, Utens EM, Verhulst FC, Ormel J, Ferdinand RF. Maternal depressive symptoms, and not anxiety symptoms, are associated with positive mother–child reporting discrepancies of internalizing problems in children: a report on the TRAILS Study. Eur Child Adolesc Psychiatry 2010;19(4):379-88. Cooper PJ, Tomlinson M, Swartz L, Woolgar M, Murray L, Molteno C. Post-partum depression and the mother-infant relationship in a South African peri-urban settlement. Br J Psychiatry 1999;175(6):554-8. Tomlinson M, Cooper P, Murray L. The Mother–Infant Relationship and Infant Attachment in a South African Peri-Urban Settlement. Child Dev 2005;76(5):1044-54. DeMulder EK, Radke-Yarrow M. Attachment with affectively ill and well mothers: Concurrent behavioral correlates. Dev Psychopppathol 1991;3(03):227-42. Winnicott DW. The theory of the parent-infant relationship. Int Rev Psychoanal 1960;41(6):585-95. Petrozzi A, Gagliardi L. Anxious and depressive components of Edinburgh Postnatal Depression Scale in maternal postpartum psychological problems1). J Perinat Med 2013;41(4):343-8. Black MM, Baqui AH, Zaman K, McNary SW, Le K, Arifeen SE, et al. Depressive symptoms among rural Bangladeshi mothers: implications for infant development. J Child Psychol Psychiatry 2007;48(8):764-72. McCrory C, McNally S. The effect of pregnancy intention on maternal prenatal behaviours and parent and child health: results of an irish cohort study. Paediatr Perinat Epidmiol 2013;27(2):208-15. Field T. Infants of depressed mothers. Devpsychopathol 1992;4(01):49-66. Murray L, Cartwright W. The role of obstetric factors in postpartum depression. J Reprod Infant Psychhol 1993;11(4):215-9. Tronick EZ. Emotions and emotional communication in infants. Am Psychol 1989;44(2):112. Rovee-Collier C. Time windows in cognitive development. DEV Psychol 1995;31(2):147. van IJzendoorn M. Attachment at an early age (0-5) and its impact on children’s development. Encyclopedia on Early Childhood Development. 2005:1-5. Brody GH, Flor DL. Maternal resources, parenting practices, and child competence in rural, single-parent African American families. Child Dev 1998:803-16. Hane A, Fox N. Natural variations in maternal caregiving of human infants influence stress reactivity. Psychol Sci 2006;17:550-6. Keim SA, Daniels JL, Dole N, Herring AH, Siega-Riz AM, Scheidt PC. A prospective study of maternal anxiety, perceived stress, and depressive symptoms in relation to infant cognitive development. Early Hum Dev 2011;87(5):373-80. Kurstjens S, Wolke D. Effects of maternal depression on cognitive development of children over the first 7 years of life. J Child Psychol.Psychiatry 2001;42(05):623-36. Campbell SB, Cohn JF, Meyers T. Depression in first-time mothers: mother-infant interaction and depression chronicity. Dev Psychol 1995;31(3):349. Sameroff AJ, Seifer R, Baldwin A, Baldwin C. Stability of intelligence from preschool to adolescence: The influence of social and family risk factors. Child Dev 1993;64(1):80-97. Murray L, Halligan S, Cooper P. Effects of postnatal depression on mother–infant interactions and child development. Wiley-Blackwell Handbook of Infant Development, The, Volume 2, Second Edition 2010:192-220.